2021
DOI: 10.3389/fpos.2021.672362
|View full text |Cite
|
Sign up to set email alerts
|

Young Rebels Who Do Not Want a Revolution: The Non-participatory Preferences of Fridays for Future Activists in Finland

Abstract: Young people’s lack of participation in elections has been taken as a sign that the young are wary of representative democracy and reject traditional authorities. Instead of election participation, it is expected that the young want more possibilities for direct involvement in political decision-making. Fridays for Future (FFF) is a global, youth-led climate movement that has been able to mobilize millions of young people around the world into political action (de Moor et al., 2020; Wahlström et al., 2019) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Second, we also contribute to a recent stream of literature investigating the motivational (preferences and beliefs) structure underlying climate protest participation. Climate protesters tend to be instrumentally (i. e. to attain a change of public policy) motivated (de Moor et al, 2020;Cologna et al, 2021), although there is regional and individual heterogeneity about advocated means (Beer, 2020;Svensson and Wahlström, 2021;Huttunen, 2021;Soliev et al, 2021), but there is also a strong affectiveemotional basis, revolving around feelings of worry, anxiety, frustration, and anger (Wahlström et al, 2019;de Moor et al, 2020), and a perceived moral duty to act (Fernandes-Jesus et al, 2020;Wallis and Loy, 2021). Social expression and self-signaling, identification, and event enjoyment also play a role (Walgrave et al, 2012;Fernandes-Jesus et al, 2020;Wallis and Loy, 2021;Cologna et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we also contribute to a recent stream of literature investigating the motivational (preferences and beliefs) structure underlying climate protest participation. Climate protesters tend to be instrumentally (i. e. to attain a change of public policy) motivated (de Moor et al, 2020;Cologna et al, 2021), although there is regional and individual heterogeneity about advocated means (Beer, 2020;Svensson and Wahlström, 2021;Huttunen, 2021;Soliev et al, 2021), but there is also a strong affectiveemotional basis, revolving around feelings of worry, anxiety, frustration, and anger (Wahlström et al, 2019;de Moor et al, 2020), and a perceived moral duty to act (Fernandes-Jesus et al, 2020;Wallis and Loy, 2021). Social expression and self-signaling, identification, and event enjoyment also play a role (Walgrave et al, 2012;Fernandes-Jesus et al, 2020;Wallis and Loy, 2021;Cologna et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This shows a conundrum for ensuring democratic responsiveness for the concerns voiced by people concerned about the future, but with low trust in the existing political system. As Huttunen (2021) shows, involvement in elite challenging activities does not necessarily entail that these activists reject the traditional representative system or that they want more participatory democracy. Nevertheless, as they exceedingly rely on activities not aimed at formal political decision-makers, there is a risk that their concerns are neglected, further exacerbating their dismay with the functioning of the political system.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it cannot be taken for granted that non-institutionalized participation entails a disdain for future consequences. For example, engagement in Fridays for Future protests was driven by intense long-term worries over climate change (Huttunen, 2021). According to this line of reasoning, we may expect that CFC-Future has a positive association with non-institutionalized participation as well.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Gaborit (2020) also found variance in terms of radicalism, and young people who were further left were more willing to critique capitalism. Piispa and Kiilakoski (2021) found that young people coalesced around the notion of "moderation" and "slowing down", while Huttunen (2021) found that young people wanted favored more responsive politicians over a deeper political revolution-not particularly radical ideas.…”
Section: How Young People Understand Climate Changementioning
confidence: 99%